A novel whole blood coagulometer for NOAC testing. (25th November 2020) - Bakhru, S; Jiang, X; Chen, L; Wang, Y; Osmani, D; Mootoo, D; Ansell, J; Zappe, S
Abstract: Background: While use of the non-vitamin K antagonist oral anticoagulants (NOACs) does not currently require routine coagulation monitoring, this can be highly desirable in at-risk patients, including those suffering major trauma or having to undergo emergency surgery, especially when a NOAC reversal agent is used. However, a point-of-care (PoC) device for the rapid measurement of clotting times in patients on NOACs is currently not available. Purpose: To characterize the sensitivity of a novel PoC coagulometer to NOAC-induced anticoagulation, as well as quantify instrument precision, via venous whole blood samples freshly spiked with rivaroxaban, apixaban and edoxaban. Methods: This study was conducted using healthy volunteers with normal coagulation lab values, including PT/INR and aPTT, confirmed via laboratory testing. Whole blood samples from two volunteers per NOAC were spiked with either 0 (sham), 75, 150, or 300 ng/mL of rivaroxaban, apixaban or edoxaban, in randomized order, each day for five days of testing. Each day, each spiked sample was run on five PoC coagulometers simultaneously for replicate measurement. Results: PoC coagulometer clotting times exhibited a high degree of linearity spanning the measuring range, with R 2 values approaching 1, and high sensitivity across NOAC concentrations tested (i.e. each concentration was statistically significantly different from the others), as well as a high level of precision across the five days of testing. Furthermore, the PoC coagulometer yielded notably low %CVs at each concentration tested, for each subject and anticoagulant, ranging from approximately 3–7% (Fig. 1, rivaroxaban and apixaban data from individual subjects shown). Conclusions: These results suggest that this PoC coagulometer could be a valuable tool to assess the pharmacodynamic effects of the NOACs in emergency and other settings. The PoC coagulometer yields results within minutes at a patient's bedside, requiring only a drop of whole blood. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Perosphere Technologies Inc.